Julius Caesar; A Midsummer-night's dream. - Shakespeare, William; L.W. Singer Company (Midsummer-night's dream, 1942)
Includes a brief history of the drama, a biography of William Shakespeare and an explanation of the dramatic techniques of plot, construction, scenes, and characterization.
Includes a brief history of the drama, a biography of William Shakespeare and an explanation of the dramatic techniques of plot, construction, scenes, and characterization.
Keywords: Drama / Study and teaching